A promising new class of irradiation tolerant materials: Ti2ZrHfV0.5Mo0.2 high-entropy alloy. Issue 3 (March 2019) - Lu, Yiping; Huang, Hefei; Gao, Xuzhou; Ren, Cuilan; Gao, Jie; Zhang, Huanzhi; Zheng, Shijian; Jin, Qianqian; Zhao, Yonghao; Lu, Chenyang; Wang, Tongmin; Li, Tingju
Abstract: Recently, high-entropy alloys (HEAs) or multi-principal-element alloys with unprecedented physical, chemical, and mechanical properties, have been considered as candidate materials used in advanced reactors due to their promising irradiation resistant behavior. Here, we report a new single-phase body-centered cubic (BCC) structured Ti2 ZrHfV0.5 Mo0.2 HEA possessing excellent irradiation resistance, i.e., scarcely irradiation hardening and abnormal lattice constant reduction after helium-ion irradiation, which is completely different from conventional alloys. This is the first time to report the abnormal XRD phenomenon of metallic alloys and almost no hardening after irradiation. These excellent properties make it to be a potential candidate material used as core components in next-generation nuclear reactors. The particular irradiation tolerance derives from high density lattice vacancies/defects.